TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN DI PMB SUPADMI, SST, MSi, DESA KUNDEN, BULU, SUKOHARJO - N. Kadek Sri Eka Putri; Hastutik Tutik (Jurnal Ilmiah Maternal, 2021)
One of the common psychological disorders experienced by pregnant women is anxiety. At the gestational age of seven months and over, the level of anxiety of pregnant women is increasingly acute and intense as the baby's birth approaches. Anxiety and fear before childbirth are the most frequently experienced by mothers during pregnancy (Maramis, 2005; Hasuki, 2007). The purpose of this study was to determine the level of anxiety of third trimester pregnant women in facing childbirth at PMB Supadmi, SST, MSi in Kunden Village, Bulu, Sukoharjo. The research method used is descriptive. The research location was carried out at PMB Supadmi, SST, MSi in Kunden Village, Bulu, Sukoharjo, from March to May 2021. The sample used in this study was 28 respondents. Anxiety measurement uses the HARS questionnaire with 16 questions. To analyze the data using univariate analysis, namely analyzing the existing variables descriptively by calculating the distribution of frequencies and proportions to determine the anxiety level of pregnant women. From the results of the study it was found that the majority of respondents with moderate, severe and very severe levels of anxiety each numbered 7 respondents (25.0).